Flushing After Lumbar Epidural Steroid Injection with Dexamethasone - Shermon, Suzanne; Van Acker, Gustaf; Suric, Vladimir; Kim, Chong; Abd-Elsayed, Alaa; Mata, Nicholas (Current pain and headache reports, 2023)
Purpose of Review Epidural steroid injections are an accepted treatment for low back pain and radicular symptoms. While epidural steroid injections are routinely performed without complications, side effects can be seen, including flushing. Flushing has been studied using various steroid preparations, including dexamethasone, but at significantly higher doses. This was a prospective cohort study that examines the rate of flushing in ESIs with a lower dose (4 mg) of dexamethasone. Subjects undergoing lumbar epidural steroid injection were asked about the presence of flushing following the procedure prior to discharge and again at 48 h after. A total of 80 participants received fluoroscopically guided interlaminar and transforaminal epidural injections. All participants received 4 mg of dexamethasone. Of the 80 subjects, 52 were female, and 28 were male. Seventy-one underwent a transforaminal epidural injection and 9 underwent an interlaminar epidural injection. Four (5%) subjects experienced flushing—1 subject experienced immediate post-procedural flushing and 3 experienced flushing within 48 h. All 4 subjects (100%) were female. All 4 subjects received transforaminal injections (100%). Recent Findings There is a gap of knowledge about the flushing after lumbar epidural steroid injection with dexamethasone. Summary Flushing is a known and common side effect of epidural steroid injections, varying in frequency based on type of steroid as well as dose. We found 5% incidence in flushing reaction with 4 mg of dexamethasone.